The Effect of Social Adjustment Mediation on Relationships Homesickness with The Happiness (Universitas Negeri Semarang, 2019)
This research aim was to test the effect of homesickness on social adjustment and happiness, as well as the effects of homesickness mediation with happiness through social adjustment. The samples involve 378 students of Senior High School with the boarding school system selected using random cluster sampling. Structural equation models are used to examine the effect of direct homesickness relationships on happiness and the effect of indirect relationships through social adjustment. The research method used is a structural equation model. The results showed the effect of social adjustment mediation in connecting with homesickness and happiness. Furthermore, homesickness directly can predict social adjustment; homesickness negatively predicts happiness and adjustments to social positively predict happiness. The implications of the research findings are discussed in the article.